The Ali Masjid Group, Jamrud, Khyber Agency - Khan, Muhammad Attaullah (Journal of Himalayan Earth Sciences, 1970)
Of all the formations exposed in the north of Jamrud, the Ali Masjid Formation is the most diverse lithologically. A detailed work revealed that the so-called Ali Masjid Formation contains many well-defined and stratigraphically valid formations. As such the Ali Masjid Formation is considered here as a group. Evidence for this conclusion consists of: (i) The snowy white and grayish-white quariziies, which form the base of the group, ore traceable over most of the Khyber Agency, Mulla Gori, and in Hazara. (ii) The Kandar Phylliie, a formation of considerable disribution, ranges in thickness from 600 to 900 feet. Both lithologically and palaeotologically, it is distinguishable from the underlying and the overlying rocks. (iii) The Ghundai Sar Reef, already recognized as the Nowshera Formation (Siluro-Devonian), forms a part of the Ali Masjid Group. (iv) The quartzite conformably overlying the Nowshera and other reef carbonates and measuring about 600 feet in thicknrss is recognized as the Misri Banda Quartzite. (11) Thr Warran Ghundai Fortmation, about 1,200 feet thick, is both lithologically and palaeontologically different from other formations exposed in the area. It represenrs varieties of enrironmeni of deposition.